2013
DOI: 10.3109/00498254.2013.867553
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric rodents with humanized liver: bridging the preclinical/clinical trial gap in ADME/toxicity studies

Abstract: 1. Immunocompromised mice with humanized livers were developed in the mid-1990s to allow the study of human hepatotropic viruses, which normally replicate only in higher primates. The production of the uPA/SCID mouse was the vanguard of these models and remains the most widely worked upon model for an ever increasing range of applications. 2. Since toxicology is conducted in laboratory animal species with the implicit intent of predicting the outcome of accidental, or intentional, human exposure, the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 129 publications
0
29
0
Order By: Relevance
“…In this context, an additional factor contributing to the broad use of rodents as first-line in vivo models for pharmacological testing is the availability and the established methods for de novo generation of genetically modified mice (with a gene-knockout, downregulation (knockdown), or overexpression of a protein of interest), as well as genetically modified rats, which are providing a set of additional approaches to study pharmacological effects. Such genetically modified rodent models are successfully applied for the verification of in vivo efficacy prior to human trials, for the discovery of new pharmacological targets, as well as to assist the elucidation of pharmacological mechanisms of action (Foster et al, 2014;Zambrowicz and Sands, 2003;Zhang et al, 2012). The generation of genetically modified animal models has dramatically evolved recently by the development of new TALEN-and CRISPR/Cas9-mediated techniques for genome editing Miller et al, 2011;Wang et al, 2013a).…”
Section: Considerations Regarding the Choice Of Bioassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, an additional factor contributing to the broad use of rodents as first-line in vivo models for pharmacological testing is the availability and the established methods for de novo generation of genetically modified mice (with a gene-knockout, downregulation (knockdown), or overexpression of a protein of interest), as well as genetically modified rats, which are providing a set of additional approaches to study pharmacological effects. Such genetically modified rodent models are successfully applied for the verification of in vivo efficacy prior to human trials, for the discovery of new pharmacological targets, as well as to assist the elucidation of pharmacological mechanisms of action (Foster et al, 2014;Zambrowicz and Sands, 2003;Zhang et al, 2012). The generation of genetically modified animal models has dramatically evolved recently by the development of new TALEN-and CRISPR/Cas9-mediated techniques for genome editing Miller et al, 2011;Wang et al, 2013a).…”
Section: Considerations Regarding the Choice Of Bioassaysmentioning
confidence: 99%
“…Although such large animal models are associated with limitations, such as higher price and more pronounced ethical considerations, their use is still widely practiced, especially by the pharmaceutical industry, since the regulatory guidelines of FDA, European EMA, and other similar international and regional authorities usually require safety testing in at least two mammalian species, including one non-rodent species, prior to human trials authorization (Parasuraman, 2011;van der Laan et al, 2010). Indeed, rodent and human proteins are sometimes not similarly sensitive toward bioactive compounds (Huang et al, 2004;Kervinen et al, 2010), and therefore a higher confidence for safety and efficacy can be obtained by using several mammalian species, or genetically engineered "humanized" animal models if available (Foster et al, 2014;Scheer and Roland Wolf, 2013). In this context, an additional factor contributing to the broad use of rodents as first-line in vivo models for pharmacological testing is the availability and the established methods for de novo generation of genetically modified mice (with a gene-knockout, downregulation (knockdown), or overexpression of a protein of interest), as well as genetically modified rats, which are providing a set of additional approaches to study pharmacological effects.…”
Section: Considerations Regarding the Choice Of Bioassaysmentioning
confidence: 99%
“…The combination of severe immunodeficiency defects in mice with a gene knockout or an expressed transgene causing damage to endogenous murine liver cells facilitates the engraftment and proliferation of transplanted human liver cells in the mouse liver [33]. The repopulated ‘humanized' liver contains both mouse and human hepatocytes in various proportions depending on the model considered.…”
Section: Animal Models For Predicting Dili?mentioning
confidence: 99%
“…Initially developed as models of HBV and HCV infection or Plasmodium falciparum infestation, this model has been used to study drug metabolism and, more recently, liver toxicity [33]. …”
Section: Animal Models For Predicting Dili?mentioning
confidence: 99%
“…Studies have demonstrated that uPA/SCID chimeric mice livers have expression levels and enzymatic activity for major human P450s and phase II conjugation enzymes similar to that in donor human hepatocytes (Katoh et al, 2004(Katoh et al, , 2005bTateno et al, 2004;Nishimura et al, 2005) and demonstrate a human-like susceptibility to CYP450 inhibition (Katoh et al, 2004(Katoh et al, , 2007 and induction (Katoh et al, 2005a,c;Emoto et al, 2008). There have also been some attempts to evaluate whether these mice can recapitulate the in vivo human metabolic profile of various xenobiotics (Foster et al, 2014). Some examples of these studies include CYP2D6-mediated metabolism of debrisoquine to 4-hydroxy debrisoquine (Katoh et al, 2007), CYP2C9-catalyzed conversion of S-warfarin to 7-hydroxywarfarin (Inoue et al, 2008(Inoue et al, , 2009, comparison with human metabolic profile of three different GSK drug candidates (De Serres et al, 2011), metabolism of ibuprofen and naproxen (Sanoh et al, 2012), and aldehyde oxidase-catalyzed oxidation of zaleplon (Tanoue et al, 2013).…”
Section: Introductionmentioning
confidence: 99%